Development of Target Basket Tools for Set-Up and Receive Serve Precise Practice in Volleyball Games (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2018)
The purpose of this research is to make design and know the effectiveness of target basket tool which is developed. The research methodology used is research and development. The results showed the quality of the product, based on a volleyball expert's evaluation obtained a mean score of 92.8 with the criteria